Hydrogen solubility in biphasic liquid reaction mixture of cinnamaldehyde hydrogenation: experimental and mathematical modeling study - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Journal of Chemical Sciences, 2022)
The solubility of hydrogen in the biphasic reaction mixture of cinnamaldehyde hydrogenation at 298 to 353 K has been determined in this work experimentally and by using a thermodynamic model. It is evident from many studies that the addition of extra phase, aqueous KOH as the fourth phase, to the three-phase cinnamaldehyde hydrogenation mixture [gas (hydrogen)-liquid (cinnamaldehyde + toluene)-solid (catalyst)] leads to enhancement of cinnamyl alcohol selectivity to a great extent. Determination of hydrogen solubility in this biphasic (organic-aqueous) reaction mixture is crucial to understand the intrinsic reaction kinetics of this reaction. The solubility of hydrogen was experimentally determined using a pressure drop method and reported in terms of Henry's constant. Firstly, hydrogen solubility was determined in pure components viz. toluene, cinnamaldehyde, and water followed by determination of its solubility in the cinnamaldehyde-toluene mixture, aqueous KOH, and eventually, in the reaction mixture containing the two immiscible liquid phases. The effect of changing concentrations in these mixtures and changing phase holdups in the total reaction mixture on hydrogen solubility was studied. Starting from pure components to the reaction mixture, the hydrogen solubility was predicted using a two-step thermodynamic approach involving regular solution theory and the theory of corresponding states. The solubility predictions from this thermodynamic model will be helpful in the accurate estimation of kinetic parameters.
Keywords: biphasic liquid mixture; gas-liquid-liquid-solid [GLLS]; hydrogen solubility; Hydrogenation; thermodynamic model